The Polymerase Chain Reaction with Sequence Specific Primers for the Detection of the Factor V Mutation Associated with Activated Protein C Resistance - Kirschbaum, Nancy E; Foster, Paul A (Thrombosis and Haemostasis, 1995)
The prevalence of the Factor V (FV) mutation associated with activated protein C resistance (FV Leiden) and its significance as a genetic risk factor for venous thrombosis have necessitated the development of a simple, rapid, and accurate assay for its detection. The polymerase chain reaction with sequence specific primers (PCR-SSP) provides a powerful technique for the discrimination of alleles resulting from single base substitutions. PCR amplification was performed using a sense primer complementary to both FV alleles coupled with either of two antisense allele specific primers, one complementary to the normal FV allele and one complementary to the FV Leiden allele. PCR conditions were developed that favored amplification only in the case of perfect complementation between template DNA and allele specific primer. The FV genotype was assigned based on whether or not each allele specific primer set produced an amplified product. Assignment of genotypes correlated 100% with those determined by the method of PCR amplification followed by MnII digestion. PCR-SSP allows the rapid and accurate identification of carriers of the Factor V Leiden mutation by a simple PCR reaction without the need for the usual post-amplification specificity step.